Controlled attenuation parameter for the diagnosis of steatosis in non‐alcoholic fatty liver disease. Issue 4 (April 2016) - Lédinghen, Victor de; Wong, Grace Lai‐Hung; Vergniol, Julien; Chan, Henry Lik‐Yuen; Hiriart, Jean‐Baptiste; Chan, Anthony Wing‐Hung; Chermak, Faiza; Choi, Paul Cheung‐Lung; Foucher, Juliette; Chan, Carmen Ka‐Man; Merrouche, Wassil; Chim, Angel Mei‐Ling; et al.
Abstract: Background and Aim: Controlled attenuation parameter (CAP) evaluated with transient elastography (FibroScan) is a recent method for non‐invasive assessment of steatosis. Its usefulness in non‐alcoholic fatty liver disease (NAFLD) is unknown. We prospectively investigated the performance of CAP for the diagnosis of steatosis in NAFLD, factors associated with discordances between CAP and steatosis grades, and relationships between CAP and clinical or biological parameters. Methods: All CAP examinations performed in NAFLD patients with a liver biopsy performed within 1 week of CAP measurement were included. Liver biopsies were assessed for activity and fibrosis stage, NAFLD activity score, and steatosis graded as follows: S0, steatosis < 5%; S1, 5–33%; S2, 34–66%; S3, >66%. Results: Two hundred sixty‐one patients (59% male, age 56 years) from two ethnic groups were included. No patient had steatosis < 5%. The area under the receiver‐operating characteristics curve of CAP for steatosis ≥S2 and S3 was 0.80 and 0.66, respectively. At a cut‐off value of 310 dB/m, the sensitivity, specificity, and positive and negative predictive values for ≥S2 steatosis were 79%, 71%, 86%, and 71%, respectively. Discordance of at least one grade between CAP and steatosis was observed in 81 patients. By multivariate analysis, only steatosis S2S3 was associated with no discordance. By multivariate analysis, only BMI ≥ 30 kg/m 2 was significantly associated with CAP > 310 dB/m. Conclusion: The association of CAP with steatosis, especially in patients with non‐alcoholic steatohepatitis, and with elevated BMI could be useful for the diagnosis and follow‐up of NAFLD patients.